2017
DOI: 10.5455/ijlr.20170918041734
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Manipulate Progesterone for Improved Ovarian and Fertility Responses in Bovines - A Review

Abstract: Progesterone (P 4 ) is a steroid hormone primarily secreted by the Corpus luteum (CL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Exposure to an insufficient circulating level of P4 during the growth of the ovulatory follicle is one of the important factors that affect fertility in high producing animals. P4 has a negative feedback effect on LH secretion and it is believed that subluteal phase plasma P4 concentrations result in elevated LH pulse-frequency [20]. It has previously been suggested that low progesterone during early embryonic development may cause pregnancy failure and thereby reduce the pregnancy rate [33].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to an insufficient circulating level of P4 during the growth of the ovulatory follicle is one of the important factors that affect fertility in high producing animals. P4 has a negative feedback effect on LH secretion and it is believed that subluteal phase plasma P4 concentrations result in elevated LH pulse-frequency [20]. It has previously been suggested that low progesterone during early embryonic development may cause pregnancy failure and thereby reduce the pregnancy rate [33].…”
Section: Introductionmentioning
confidence: 99%